Companion plants for conservative management of Tupiocoris cucurbitaceus (Spinola 1852) (Heteroptera: Miridae: Dicyphini) on greenhouse tomato crops - Burla, Juan P.; Arbulo, Natalia; Aldabe, Joaquín; Fagúndez, César; Castiglioni, Enrique (Entomological Communications, 2022)
In recent decades, greenhouse crops relevance increased due to the high demand for products outside their growing season, with tomato standing out as one of the most cultivated crops. In these production systems, insects and mites find optimal conditions for their development, achieving high populations that affect crops. Farmers usually control these populations using chemical insecticides, which affect the health of workers and consumers and have negative effects on the environment. Tomato crops suffer damage by lepidopterans and hemipterans, among which those known as whiteflies (Hemiptera: Aleyrodidae) perform regular attacks, causing yield and quality losses in the final product. Currently, the use of zoophytophagous predators of the Miridae family, Dicyphini tribe, as an alternative for their biological control, has intensified studies on Tupiocoris cucurbitaceus (Spinola, 1852), a predator of several species of aphids and whiteflies found in Uruguay. A strategy for the conservative management of those species was designed, using companion plants grown together with the crop. By the time the tomato plants were transplanted, Calendula officinalis, Smallanthus connatus, Tithonia rotundifolia, Nicotiana tabacum, Physalis peruviana and Petunia hybrida plants were established as companion species. These plants were monitored weekly together with the tomato plants, and a greater presence of T. cucurbitaceus in the crops with companion plants was found. The results suggest that the incorporated plants were useful for the preservation and retention of predaceous mirids in productive conditions.